(untitled) (Global Journal of Medical Research, 2023)
Parkinson s disease is a neurodegenerative disease characterized by dopamine depletion death of the dopaminergic neurons of the substantia nigra of the nigrostriatal pathway and presence of neurofibrillary inclusion in the active neurons The black substance is interconnected with all regions of the brain they receive glutamatergic innervations and send direct and indirect projections modulating the activity of the dopaminergic neurons so the loss of dopamine in the striatum causes monoaminergic chemical changes leading to the increase and decrease of neuronal activity in the motor areas of the cerebral cortex